Improving Vietnam's Sustainability : Rural Road Pavement and Surfacing Design Options - World Bank (Washington, DC, 2014)
Recent research in S E Asia and Vietnam in particular, funded by the World Bank and DfID since 2003, has focused on improving rural community access through more sustainable low volume rural road design. More appropriate design ensures that roads built are cost effective in terms of whole life performance. Because of increasing recognition that gravel surfacing was not always the best solution for rural roads in Vietnam, the initial research focused on the performance of existing unsealed roads and the identification of sustainable alternatives. Subsequent research has focused on the relative performance of the alternative option trials and their role in providing a more climate resilient rural infrastructure. In general, this work has concentrated on a range of pavements to establish the best performance within a range of physical and socio-economic environments. This note highlights the findings of the Rural Road Gravel Assessment Programme (RRGAP) and the Rural Road Surfacing Trials (RRST phases I, II and III) undertaken within Vietnam under the umbrella of the Ministry of Transport Rural Road Surfacing Research (RRSR) committee. Outcomes were enhanced by information from complimentary projects within Lao PDR and Cambodia.